2017
DOI: 10.1016/j.neuropharm.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator-activated receptor alpha agonist fenofibrate attenuates alcohol self-administration in rats

Abstract: Fibrates are a class of medications used to treat hypercholesterolemia and dyslipidemia that target nuclear peroxisome proliferator-activated receptors (PPARs). Studies have shown the PPARα agonist fenofibrate decreases voluntary EtOH consumption however its impact on the reinforcing and motivational effects of EtOH is unknown. We evaluated the ability of fenofibrate (25, 50 and 100mg/kg), to alter EtOH (10%, w/v) and sucrose (2%, w/v) operant self-administration in rats under a FR2 schedule of reinforcement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…It has also shown specificity in confirming lack of efficacy for modafinil , a drug approved to help wakefulness but previously found ineffective for smoking cessation (Schnoll et al, 2008). Our procedure also recently found no evidence of efficacy for cessation with fenofibrate (Perkins et al, 2016), FDA-approved for lipid control and similar to fibrate drugs shown in preclinical research to reduce selfadministration of nicotine in rodent and primate models (Panlilio et al, 2012) and of alcohol in rodents (Haile and Kosten, 2017). Therefore, despite the potential promise of preclinical findings that suggest that stimulation of α7 nAChR reduces nicotine reinforcement and reward (Brunzell and McIntosh, 2012;Brunzell et al, 2014;Harenza et al, 2014), results of the current clinical studies indicate this Janssen α7 nAChR PAM, at the dose and duration tested, lacks clinical efficacy in aiding ability of dependent smokers to quit smoking.…”
Section: Discussionsupporting
confidence: 57%
“…It has also shown specificity in confirming lack of efficacy for modafinil , a drug approved to help wakefulness but previously found ineffective for smoking cessation (Schnoll et al, 2008). Our procedure also recently found no evidence of efficacy for cessation with fenofibrate (Perkins et al, 2016), FDA-approved for lipid control and similar to fibrate drugs shown in preclinical research to reduce selfadministration of nicotine in rodent and primate models (Panlilio et al, 2012) and of alcohol in rodents (Haile and Kosten, 2017). Therefore, despite the potential promise of preclinical findings that suggest that stimulation of α7 nAChR reduces nicotine reinforcement and reward (Brunzell and McIntosh, 2012;Brunzell et al, 2014;Harenza et al, 2014), results of the current clinical studies indicate this Janssen α7 nAChR PAM, at the dose and duration tested, lacks clinical efficacy in aiding ability of dependent smokers to quit smoking.…”
Section: Discussionsupporting
confidence: 57%
“…Fibrates increase the oxidation rate of fatty acids; therefore, they are widely used clinically for the treatment of hypertriglyceridemia (Cignarella et al, 2006). Several authors have reported that fenofibrate decreases ethanol intake in rodents (Barson et al, 2009;Karahanian et al, 2014;Blednov et al, 2015Blednov et al, , 2016Haile and Kosten, 2017;Rivera-Meza et al, 2017). We were able to demonstrate that fenofibrate increases catalase and alcohol dehydrogenase activities in the liver, which leads to rapid acetaldehyde accumulation when the animals drink ethanol (Karahanian et al, 2014;Rivera-Meza et al, 2017;Muñoz et al, 2020).…”
Section: Introductionmentioning
confidence: 60%
“…PPARα is upstream of diverse genes that are modulated by ethanol or involved in ethanol-induced effects (Ferguson et al, 2014). Preclinical studies showed that modulation of PPARα by the synthetic agonist fenofibrate reduced motivational and reinforcing properties of ethanol, as measured by voluntary drinking in mice (Ferguson et al, 2014;Blednov et al, 2016) and rats (Karahanian et al, 2015); and corroborated by the self-administration paradigm in rats (Haile and Kosten, 2017). Considering that fibrates are approved for medical conditions, these studies suggest that regulation of PPARα deserves further clinical investigation in AUD, as recently detailed elsewhere (Karahanian et al, 2015;Matheson and Le Foll, 2020).…”
Section: Role Of Naes and Pparα In Alcohol Use Disordermentioning
confidence: 94%